The way way back - Faxon, Nat; Rash, Jim, 1970-; James, Liam; Collette, Toni; Carell, Steve, 1962- (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2013)
When an awkward fourteen-year-old boy goes on a summer vacation with his mother and her boyfriend, he befriends the owner of a water park and begins to find his own identity.
Originally released as a motion picture in 2013.
Dolby digital 5.1, wide screen 1.85:1.
Features: deleted scenes, behind-the-scenes featurettes.
Liam James, Toni Collette, Steve Carell, Allison Janney, AnnaSophia Robb.
MPAA rating: PG-13.
In English, French, or Spanish with optional English, French, or Spanish subtitles.
Keywords: Teenage boys -- Drama; Coming of age -- Drama; Fiction films; Coming of age films; Feature films; Comedy films